Discussion "The Power and Architecture" - Grigoryeva, Elena; Lidin, Konstantin; Rappaport, Alexander (project baikal, 2016)
Discussion participants: Elena Grigoryeva, Konstantin Lidin, Alexander Rappaport, Dmitry Khmelnitsky and Elena Bagina